Analysis and modelling of solar evaporator collector - Mohd. Amin, Zakaria; Hawlader, Mohammad Nurul Alam; Ye, Shaochun (IIUM Press, 2015)
Solar energy is considered a sustainable resource and it has little or no harmful effects on the environment. The performance of a solar system depends to a great extent on the collector used for the conversion of solar radiant energy to thermal energy. A solar evaporator-collector (SEC) is basically an unglazed flat plate collector where refrigerant, like R134a, is used as the working fluid. As the operating temperature of SEC is very low, it utilizes both solar irradiation and ambient energy leading to a much higher efficiency than the conventional collectors. This capability of SEC to utilize ambient energy also enables the system to operate at night. This type of collector can be locally made and relatively much cheaper than the conventional collector. At the National University of Singapore, the evaporator-collector was integrated to a heat pump and the performance was investigated for several thermal applications: (i) water heating, (ii) drying and (iii) desalination. A 2-dimensional transient mathematical model of this system was developed and validated by the experimental data. The present study provides a comprehensive study of performance.